Gender-Based EFL Students’ Speaking Anxiety: Poetry Performance - Femilia, Praptika Septi; Yusuf, David Ilham (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2023)
English for Foreign Language (EFL) teachers do not always recognize students’ speaking anxiety. Meanwhile, a set of studies revealed that there was no significant difference of male and female’s students’ speaking anxiety level. In fact, male and female students have difference condition on their learning style as well as psychological performance. This study aims to examine how difference male and female EFL students’ speaking anxiety in a different context, in which the exposure was taken under the students’ performance on reciting poetry through Youtube for their Creative Writing class. It is a quantitative study with causal-comparative research design. It was carried out to 64 students fifth semester EFL students majoring in English Language Teaching (ELT) in a state Islamic University in Jember, selected by using purposive random sampling. The data were collected by using a modified questionnaire consists of 21 items of Foreign Language Classroom Anxiety Scale (FLCAS) which was originally developed by Horwit et.al. (1986). The data were analyzed by using SPSS version 24 with Mann Whitney formula computation. The results indicated that there was no significant difference between male and female speaking anxiety through their poetry performance (Sig 2 tailed 0.657 > 0.05). The mean and median scores of both also showed that they were not significantly different one into another with most samples on moderate level. The findings of this study might be used as input to further researchers to examine factors affecting speaking anxiety on male and female students.